Análisis de errores en la producción escrita de los aprendices polacos de español: las preposiciones - Fernández Jódar, Raúl (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
The article analyses the prepositional system of Polish learners of Spanish interlanguage at three different levels. The author's intention is to show that in spite of wide prepositional system the errors in the use of prepositions are few. For this reason its teaching in Spanish as a foreign language classes should not create problems.
Error analysis on written production of Polish learners of Spanish: the prepositions